Assessment of counting chambers on boar sperm parameters analyzed by a CASA-Mot system - Valverde, Anthony; Madrigal-Valverde, Mónica (Agronomía Mesoamericana, 2019)
Introduction. Understanding the variability in sperm kinetic values through different chambers depths, shows the importance to create a standard for quality control methods in the artificial insemination (AI) industry. Objective. The work aimed was to evaluate the spermatozoa kinetic parameters based on different depths of the visualization chamber by means of a commercial system of computer-assisted sperm analysis, CASA-Mot. Materials and Methods. Twenty seminal doses of ten pietrain boars were used. The experimental period was from February to July 2017. The Integrated Semen Analyses System (ISAS®v1) with 50 Hz capture frequency was used. ISAS®D4C16 and ISAS®D4C20 counting chambers with a height of 16 and 20 μm respectively and pre-heated to 37 °C were employed. Results. Higher values (p<0.05) were found for all kinetic parameters when the height of the counting chamber was 20 μm. The zone effects within the counting chamber were constant between the two heights, and the variations observed in the kinetic parameters were due to a random effect of the boar. When analyzing the zone effect within the counting chamber, the first three fields of analysis showed higher curvilinear and rectilinear velocity (p<0.05) than the following fields, which is attributed to the presence of passive movement (drifting). Conclusion. The greater amplitude and volume capacity within the counting chamber (20 μm versus 16 μm), could promote the unrestricted movement of the cells, which would explain the increase in the kinetic values as the chamber height increased. Studies on the technical conditions of seminal analysis should be continued in order to standardize valuation methods with CASA systems.